Visualization and purchase. Issue 3 (8th June 2015) - Marchini, Andrea; Diotallevi, Francesco; Paffarini, Chiara; Stasi, Antonio; Baselice, Antonio
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to present an attempt to evaluate Italian olive oil brand competition thought the analysis of consumers' visual perspective. Design/methodology/approach – Through the implementation of a new information technology system called "Visual Marketing REL", which furnishes eye-tracking measures, the authors were able to produce important information relative to the layout organization of to the Italian olive oil shelf, a strategic product of the agro-food chain. The research uses the "in situ" testing of the software developed. Findings – The research, following up the thesis of sensorial marketing affecting choices, intends to identify an IT tool to facilitate the design of the shelf by increasing the efficiency of the retail mix. Results highlight that specific positioning could impact the differentiation effect and orientate consumers' choices, thus increasing the efficiency of the retail mix. Research limitations/implications – To generalize the results would require many repetitions of different product categories. In this case, it would be possible to quantify the levels of correlation between visual information and sales. Practical implications – This work opens important considerations in terms of strategic management of modern distribution, leaders and minor brands competitive relationship, as well as opportunities for producers of high-quality products, which could address their strategies to differentiation and niche market in cooperation with retailers. Social implications – The research aims to encourage the process of consumer choice and reduce information asymmetries. Originality/value – The most important result is the connection among choices, visualization, differentiation strategy and positioning/ordering on the shelf. The layout management, in fact, could be used as a joint strategy of retailers as well as producers to emphasize quality and price differentiation, thereby increasing sales. Moreover, the study provides for the first time the outcomes of a brand new software "Visual Marketing REL", highlighting its limits and positive elements.